2019
DOI: 10.3389/fpls.2019.01051
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Loading Enhances Stress Impact of Drought on a Semi-natural Temperate Grassland

Abstract: Two important threats to the sustainable functioning of seminatural grasslands in temperate zones are (1) nutrient loading due to agricultural fertilization and pollution, and (2) the increase of extreme drought events due to climate change. These threats may cause substantial shifts in species diversity and abundance and considerably affect the carbon and water balance of ecosystems. The synergistic effects between those two threats, however, can be complex and are poorly understood. Here, we experimentally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 83 publications
(118 reference statements)
2
43
2
Order By: Relevance
“…Drought and soil water deficits are increasingly limiting factors for plant growth in many regions of the world [22]. In our study, the total precipitation of the maize-growing season in 2017 was only 39.5% of that in 2018 ( Figure 1); thus, 2017 was considered the dry year, and 2018 was considered the wet year.…”
Section: Discussionmentioning
confidence: 76%
“…Drought and soil water deficits are increasingly limiting factors for plant growth in many regions of the world [22]. In our study, the total precipitation of the maize-growing season in 2017 was only 39.5% of that in 2018 ( Figure 1); thus, 2017 was considered the dry year, and 2018 was considered the wet year.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, we investigated the plant physiological response of the abundant forb and grass species ( Centaurea jacea L., Arrhenatherum elatius (L.) P.Beauv. ex J.Presl & C.Presl, Dactylis glomerata L.) in the same grassland studied by Kübert et al (2019). We studied their response under natural, drought, N addition and combined drought and N addition conditions over the entire growing season.…”
Section: Introductionmentioning
confidence: 83%
“…Hofer et al (2017), on the other hand, discovered that N fertilization improved drought resistance of non‐legume species. In contrast, Kübert et al (2019) observed, at the community level, that N loading strongly enhanced the effect of drought stress on a grassland community. Drought‐related reduction of the grassland’s gross primary production and net ecosystem exchange was much stronger on plots with N loading, resulting in the ecosystem becoming a net carbon source.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations